Investigação da consciência metacognitiva no âmbito do desenvolvimento profissional com foco em tecnologias educacionais: um estudo com professores no contexto da pandemia da covid-19 - Nathália Dornelas Barbosa (2021)
This study arises from the need for a better understanding of the self-regulation of the cognitive process associated with learning, at the interface between Neuroscience and Education. The COVID-19 pandemic required innovative pedagogical practices and the use of Educational Technologies. With distance learning, autonomy and metacognition become crucial skills for school success. The objective was to analyse the teachers' conception of the concept and exercise of metacognition and how prepared they are in relation to the use of digital technologies. Thirty-one teachers from the public basic education network participated. Data collection and analysis were carried out within the scope of a distance course. An investigation of previous knowledge and academic training was carried out through a semi-structured questionnaire; investigations of digital skills and metacognitive awareness through the Self- Assessment of Teachers' Digital Skills, the Metacognitive Awareness Inventory and focus groups. A questionnaire was applied at the end of the course to assess learning. The reports of the Focus Group showed that teachers understand that Educational Technologies are allies of the teaching-learning process, and the construction of digital skills represents a challenge for professional training. The results obtained with the Metacognitive Consciousness Inventory showed that 42% of the teachers have metacognitive knowledge “Frequently” and 24% “Always” indicating that they have knowledge about their own cognition or about cognition in general. Regarding the regulation of cognition, 46% of the participants apply the strategies “Frequently” and 22% “Always”. As for Digital Skills, most teachers are between “familiarization” (14 of them – 45%) and “adaptation” (15 of them – 48%) in the pedagogical area. In the area of professional development, 07 professors (23%) consider that they are at the level of "familiarization", 21 professors (68%) declare to be at the level of "adaptation" and in digital citizenship most professors are distributed between "familiarization" (68%) and “adaptation” (29%). In addition, participants demonstrated reasonably high levels of metacognitive awareness, although they demonstrated low levels of digital skills. Thus, the present work brought evidence that there are significant gaps in the initial and continuing education of teachers, especially with regard to the understanding of the neurobiological process of learning, and the use of digital skills.